The motivations of external whistleblowers and their impact on the intention to blow the whistle again. (8th February 2019) - Park, Heungsik; Lewis, David
Abstract: The purpose of this study was to inquire into the relative importance of morality, cost‐benefit, and emotion as motivations for the decision to blow the whistle externally, and the effects of such factors as motivations, perceived negative consequences, and preferences for reform on the intention to blow the whistle again. Based on a literature review, we formulated some hypotheses and, to test them, we used the data collected from a survey of 127 external whistleblowers in South Korea. The results revealed that morality was the most important motivation, followed by emotion, and then cost‐benefit, which thus, seemed to be the least important for the whistleblowers. Morality as a motivation and the perceived negative consequences of whistleblowing had a significant effect on the intention to blow the whistle again. This study helps advance the understanding of the motivations behind whistleblowing and the factors that influence the intention to blow the whistle again.